Stigma Levels Toward Psychiatric Patients Among Medical Students—A Worldwide Online Survey Across 65 Countries - Babicki, Mateusz; Małecka, Monika; Kowalski, Krzysztof; Bogudzińska, Bogna; Piotrowski, Patryk (Frontiers in Psychiatry, 2021)
Background: According to epidemiological data, over 450 million people worldwide suffer from mental disorders, presenting one of the major challenges of modern medicine. In their everyday lives, patients, in addition to fighting the disease itself, often struggle with stigmatization. This phenomenon negatively affects both the diagnostic and therapeutic processes, as well as the patients’ everyday functioning. This study aimed to assess stigma attitudes towards psychiatry and psychiatric patients among undergraduate medical students. Methods: This study used a Computer-Assisted Web Interview (CAWI), which included the standardized items from the Mental Illness: Clinicians’ Attitudes (MICA-2) scale to evaluate stigma. The study was disseminated via the internet to students from medical universities from 65 countries worldwide. Participation was voluntary and anonymous. The study involved 1,216 students from these 65 countries. Most of the sample were women, and most were medical faculty students and students living in cities with more than 500,000 residents. Taking into consideration Gross Domestic Product (GDP) per capita and Human Development Index (HDI) variables, it can be seen that there was a prevalence of medical students from highly developed countries. Results: For the whole sample, the mean MICA-2 score was 40.5 points. Women and medical and nursing students showed more positive attitudes towards psychiatric patients. Students from countries with the highest economic development levels also achieved statistically lower MICA-2 scores. Lower score means a more positive attitude. Conclusion: Stigma towards both psychiatry and psychiatric patients is common among undergraduate medical students. Female students and respondents with a history of mental disorders in countries with high HDI and GDP per capita indices show more favourable attitudes than other medical students. There is a need to further our understanding of the problem of stigmatization, both among the general population and among medical personnel, and to implement and maintain appropriate measures to reduce stigma towards psychiatry.